Piano Sonata no. 12 in A-flat major, op. 26 (Simrock) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Bonn; Germany; N. Simrock)
Piano sonata no. 12 in A-flat major, op. 26, early edition published around 1802 by N. Simrock, variant.